Poly(N-vinylimidazole) based hydrogen bonded side chain liquid crystalline polymer - Gursel, Yesim H.; Senkal, Bahire Filiz; Kandaz, Mehmet; Yakuphanoğlu, Fahrettin (Wiley, 2011)
A new poly(N-vinylimidazole) (PVI) based side chain liquid crystalline polymer (HB-PLC) was prepared from PVI as a hydrogen bond acceptor polymer and 11-(4-cyanobiphenyl-4'-oxy)undekan-1-ol (LC11) by molecular self-assembly processes via hydrogen bond formation between nitrogen of PVI and hydroxyl group of the LC11. The formation of H-bond was confirmed by using FTIR spectroscopy. The liquid crystalline behavior of the HB-PLC was investigated by differential scanning calorimeter (DSC) and polarized optical microscopy. The thermal behaviors of the H-bonded liquid crystalline polymer were investigated by DSC measurements under various heating rates. The HB-PLC shows a transition temperature of 97 degrees C with an relatively high enthalpy change of 140.6 J/g corresponding to the transition from liquid crystalline nematic phase to isotropic phase. The activation energy required for liquid crystal phase transformation was found to be 551.75 kJ/mol. Copyright (C) 2010 John Wiley & Sons, Ltd.
10th International Conference on Polymers for Advanced Technologies (PAT 2009) -- OCT 11-14, 2009 -- Jerusalem, ISRAEL
Keywords: hydrogen bonding; liquid crystalline polymers; poly(N-vinylimidazole)